Law of remedies : a European perspective / edited by Franz Hofmann, Franziska Kurz. - Hofmann, Franz, 1981-; Kurz, Franziska (Writer on law) (Intersentia, 2019)
With the increasing importance of the concept of remedies in European private law, this book focuses on remedies as a distinctive and novel field of European legal research. It considers the common law tradition (England and Wales), as well as the civil law viewpoint (on the example of Germany), making the case for a European law of remedies. It is argued that 'remedies' are an enforcement tool influencing the scope of substantive rights. In doing so, the book analyses different mechanisms of enforcement, including the debate on private versus public enforcement as well as the perspective of criminal law. The enforcement of rights is understood as an intradisciplinary task. Remedial law is, however, distinct from procedural law, as well as from substantive law in a narrow sense. Subsequent to defining the scope of a law of remedies, this book analyses several underlying principles and common themes. For example, the proportionality test is presented as fundamental principle in European remedial law. The value gained by identifying common ground is e. g. illustrated with respect to damages in European Private Law. Especially in IP law, in turn, the CJEU rulings and secondary European legislation confirm the importance of proportionate remedies. Moreover, within the law of remedies the function of each remedy can be analysed, and respective interests can be balanced. Further examples that reveal the importance of a sophisticated enforcement are the CJEU's recent extension of the concept of communication to the public, the notice-and-take-down-procedure in intermediary liability cases and remedies for non-conformity of digital content or consumers' remedies in European contract law. In German patent law, the development of grace periods and shareholders ́ rights in German corporate law can be analysed from a "remedy" perspective as well. Overall this book demonstrates that remedies are more than just an addendum and innovatively presents an emerging research area. As such it is of great relevance to all lawyers concerned with questions surrounding the enforcement of rights: international academics as well as practitioners.